Role of CT Coronary Angiography at Initial Presentation in Kawasaki Disease—Insights from a Tertiary Care Center in North India - Manphool Singhal; Rakesh Kumar Pilania; Suprit Basu; Dev Desai; Abarna Thangaraj; Ripudaman Singh; Radhika Semwal; Taranpreet Kaur; Gopika Sri; Murugan Sudhakar; Arun Sharma; Pandiarajan Vignesh; et al. (Diagnostics)
Background: Kawasaki disease (KD) is a systemic vasculitis and the leading cause of acquired heart disease in children. Early identification of coronary artery abnormalities (CAAs) is crucial to guide treatment and improve outcomes. While transthoracic 2D echocardiography (TTE) remains the first-line imaging modality, it has limitations, particularly in visualizing distal coronary artery segments and detecting thrombi. Computed tomography coronary angiography (CTCA) offers enhanced visualization, but its role at initial presentation of KD remains underexplored. Methods: We reviewed the records of 71 children with KD who underwent CTCA at their initial presentation at a tertiary center between November 2013 and December 2024. The CTCA findings were compared with those of TTE. CTCA was performed after stabilization using radiation-minimized protocols. Results: Of 71 patients, 62 had CAAs on baseline TTE. CTCA confirmed CAAs in 39 patients, identified additional lesions in 23, and detected distal aneurysms and coronary branch involvement missed by TTE. In 20 patients with initially abnormal TTE, CTCA demonstrated normal coronaries, facilitating treatment de-escalation. CTCA identified coronary thrombi missed on TTE in two patients and congenital coronary anomalies in three patients. CTCA findings led to modification of therapy in multiple cases. Conclusions: CTCA is a valuable adjunct to TTE in evaluating coronary artery involvement at the time of initial presentation of children with KD. Given its superior visualization of the entire length of coronary arteries, CTCA has a vital role in therapeutic decision-making in KD.